The Effect of Job Satisfaction on Work Performance with Mediated Work Life Balance: English - Hanna Gricilia Tampubolon; Suryani Hardjo; Patisina (Yayasan Ilomata, 2026)
This study aims to examine the direct impact of job satisfaction on individual work performance, as well as the indirect influence mediated by work-life balance. The data were collected using instruments designed to assess job satisfaction and work-life balance, while work performance data were obtained from relevant institutions. The sample was obtained through convenience sampling, yielding a total of 78 employees. The findings of this study demonstrate both direct and indirect effects of job satisfaction on work performance, although the mediator work-life balance did not exert a greater effect than job satisfaction. This study contributes to the organizational and industrial context, demonstrating that job satisfaction is a key issue that needs improvement, rather than work-life balance, which is an external issue within the organizational and industrial context. Unlike previous research that demonstrated that work-life balance plays a significant role in one's work performance, this study demonstrates that job satisfaction is far more effective in improving work performance. Limitations and recommendations are explained further in this article.